2015
DOI: 10.1007/s00265-015-1965-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within honey bee colonies affects pathogen load and relative virus levels in honey bees, Apis mellifera L

Abstract: The evolution of polyandry is one of most highly debated topics in sociobiology. One hypothesis suggests genetic diversity increases resistance against the wide range of parasites and diseases affecting colonies. We investigated effects of manipulating genetic diversity on colony population size, fall Varroa population, Varroa and bee mortality rates, virus prevalence and concentration, and prevalence of Nosema apis Z. and Nosema ceranae F. Sister queens selected for resistance to Varroa were inseminated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…This hypothesis was recently tested in honey bee colonies headed by queens artificially inseminated with one or 12 drones and proved true for N. ceranae , with significantly higher prevalence levels detected in genetically similar colonies as compared to genetically diverse colonies (Desai and Currie, ). Interestingly, no significant differences between the two types of colonies were found for N. apis (Desai and Currie, ), which agrees with a previous study from Woyciechoski and Krol (). In conclusion, while all these studies represent first (but not comparable) attempts to address the role of honey bee variability in N. ceranae virulence, carefully designed cage and field infection assays with genetically characterized host and pathogen are required for a better understanding of their interaction.…”
Section: What Are the Major Effects Of N Ceranae On Honey Bees?mentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis was recently tested in honey bee colonies headed by queens artificially inseminated with one or 12 drones and proved true for N. ceranae , with significantly higher prevalence levels detected in genetically similar colonies as compared to genetically diverse colonies (Desai and Currie, ). Interestingly, no significant differences between the two types of colonies were found for N. apis (Desai and Currie, ), which agrees with a previous study from Woyciechoski and Krol (). In conclusion, while all these studies represent first (but not comparable) attempts to address the role of honey bee variability in N. ceranae virulence, carefully designed cage and field infection assays with genetically characterized host and pathogen are required for a better understanding of their interaction.…”
Section: What Are the Major Effects Of N Ceranae On Honey Bees?mentioning
confidence: 97%
“…While it remains to be demonstrated that variation among A. mellifera subspecies influences virulence of N. ceranae , it has been repeatedly shown that increased genetic diversity within a colony improves its resistance to a diverse array of diseases (Palmer and Oldroyd, ; Tarpy, ; Tarpy and Seeley, ; Seeley and Tarpy, ; Desai and Currie, ), supporting one of the hypothesis related with the evolution of polyandry (Hamilton, ). This hypothesis was recently tested in honey bee colonies headed by queens artificially inseminated with one or 12 drones and proved true for N. ceranae , with significantly higher prevalence levels detected in genetically similar colonies as compared to genetically diverse colonies (Desai and Currie, ). Interestingly, no significant differences between the two types of colonies were found for N. apis (Desai and Currie, ), which agrees with a previous study from Woyciechoski and Krol ().…”
Section: What Are the Major Effects Of N Ceranae On Honey Bees?mentioning
confidence: 99%
“…groups of bees who share the same father) with different susceptibilities to parasites and pathogens, potentially reducing their spread within the colony. For instance, honey bee colonies composed of more patrilines have lower prevalence of A. apis (Tarpy, 2003), N. ceranae (Desai & Currie, 2015) and P. larvae (Seeley & Tarpy, 2007). Likewise, the prevalence of the trypanosomatid C. bombi is reduced in genetically diversity colonies of experimentally inseminated bumblebee queens (Baer & Schmid-Hempel, 2003).…”
Section: At the Collective Levelmentioning
confidence: 99%
“…There is a need to invest in diverse kinds of research and to expect that future ecological surprises are inevitable. The possibility of the emergence of a new species of invasive varroa mite (Roberts et al 2015), changes in honey bee genetics over time and space (Desai and Currie 2015;Locke et al 2012), and the vagaries of economic and political instability (Moritz and Erler 2016) highlight the importance of maintaining an appreciation of the novelty and possibilities of the future.…”
Section: Resultsmentioning
confidence: 99%